Efeito antinociceptivo, anti-inflamatório e antioxidante do extrato etanólico das folhas de Combretum duarteanum cambess (Combretaceae) - Gouveia, Marcos Guilherme de Sousa (2011)
Combretum duarteanum Cambess is a medicinal plant from north and northeast of Brazil, know popularly as Vaqueta or Caatinga-branca . Infusions prepared with the aerial parts (stems and leaves) of C. duarteanum are used in folk medicine for the treatment of pain and as sedative. The objective of this study was to evaluate the antinociceptive, anti-inflammatory and antioxidant potentials of ethanolic extract of Combretum duarteanum (EEC). The antioxidant activity was investigated in vitro using lipid peroxidation, hydroxyl radical-scavenging, and scavenging activity of nitric oxide (NO) assays. EEC possesses a strong antioxidant potential according in these tests, and also presented scavenger activity of NO and hydroxyl. The antinociceptive activity was investigated using acetic acid-induced writhing, formalin, and hot plate tests in mice. EEC (100, 200, and 400 mg/kg; i.p.) significantly reduced the number of writhes (38.1, 90.6, and 97.8%, respectively), This extract also decrease the number of paw licks during phase 1 (30.5 and 69.5%, higher doses) and phase 2 (38.1, 90.6, and 97.8%, all doses) of a formalin test. EEC increased the latency of animals in the hot plate, effect that was reversed by naloxone, suggesting the involvement of opioid system in its mechanism of action. Administration of the EEC (200 and 400 mg/kg; i.p.) exhibited an anti-inflammatory activity in the carrageenin and arachidonic acid-induced rat paw edema test. These results indicate that the EEC has antinociceptive activity mediated by central pathways, with possible participation of the opioid system. Besides, antincociceptiva and anti-inflammatory effects associated with peripherals mechanisms, with inhibitory action of prostaglandin synthesis and the contribution of its antioxidant potential.